IDE MISKIN KE KAYA YANG TERCERMINKAN DALAM FILM A KNIGHTâ€™S TALE OLEH BRIAN HEGLAND - Filemon, Aprillio Cedrik; Sigarlaki, Stephani J.; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â This research entitled â€œRags to Riches as Reflcted in the Film A Knightâ€™s Tale by Brian Heglandâ€ It is research that focuses on Rags to Riches analysis, particulary showing the idea based on American Dream concept that riches is not the impotant element to live but happiness. In identifying, classifying, and analyzing the data, the writer uses the theory of McGlinn (2005) about the idea of rags to riches, and the theory of Literature by Wellek and Warren (1956) in order to analyze the intrinsic approach. The method employed in this research is descriptive method by Fraenkel dan Wallen (1993). The writer analyzes the idea of Rags to Riches found in the movie A Knightâ€™s Tale by looking at the characters, plot, setting, but mainly on the main character: what the person says, what the person doesincluding, what the person thinks; what others say about the main character, what others do (that may help indicating what the main character could do and does not do). The data were collected from the movie entitled A Knightâ€™s Tale. The result of this study shows that there are three elements reflected by the character of the movie regarding to the idea of Rags to Riches; they are: hardworking which divides into plan, sacrifice, and motivation; personality which consists of kindhearted, helpful, dilligent, respectful, and responsible: luck which has two types such as sudden luck and undefined luck. There are also four parts of characterization development includes personal description, opinion and disposition, talks, and reaction.Keywords: Rags to Riches, American Dream, Characterization Development.